The influence of nonsurgical periodontal therapy on the occurrence of adverse pregnancy outcomes: A systematic review of the current evidence - Rohini Govindasamy; Sugavanesh Periyasamy; Mohan Narayanan; Venkateshwarapuram Rengasamy Balaji; Manikandan Dhanasekaran; Balakrishnan Karthikeyan (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: The poor maternal oral health in the pregnancy has an impact on the fetus through the oral-systemic link. Various studies have proven the relationship between poor maternal oral health and the occurrence of adverse pregnancy outcomes. Hence, periodontal therapy becomes indispensable during pregnancy. Previous systematic reviews and meta-analysis conducted to assess the influence of periodontal therapy on the occurrence of adverse pregnancy outcomes have shown inconsistent results. Hence, we conducted the present review to assess the influence of periodontal therapy on the occurrence of adverse pregnancy outcomes including the studies published till date. Materials and Methods: We searched for the relevant studies using the databases PUBMED, MEDLINE, CINAHL, and EMBASE on the randomized controlled trials evaluating the influence of periodontal treatment on adverse pregnancy outcomes from 2000 to 2018. Nineteen studies were considered for the present review based on the predetermined criteria. The risk of bias tool by Cochrane was used to evaluate the risk of bias among the studies. Results: Among the studies included for the present review, the occurrence of preterm birth among the pregnant mothers who received periodontal therapy ranged from 0% to 53.5%, while in the control group, the range was 6.38%-72%. The rate of LBW among the mothers treated for periodontal disease ranged from 0% to 36%, and in the control group, it varied from 1.15% to 53.9%. Conclusion: With best possible evidence, it can be inferred that nonsurgical periodontal therapy is safe during pregnancy. Even though it does not completely avert the occurrence of adverse pregnancy outcomes, it can be recommended as a part of antenatal care.